2018
DOI: 10.3126/mjpahs.v1i2.23405
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal shock wave lithotripsy in the management of upper urinary tract stone: a single institute experience

Abstract: Introduction: The aim of the study was to observe the success rate of extracorporeal shock wave lithotripsy (ESWL) in the management of upper urinary tract stones. Materials and Methods: This retroprospective study was conducted in Pokhara Kidney stone Centre, Pokhara, Kaski, Nepal from January 2017 to January 2018. Seventy nine patients were selected in this study with upper urinary tract stone, size less than 20 mm. Results: Seventy four (93.67%) patients were successfully treated in initial use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
(3 reference statements)
0
2
0
Order By: Relevance
“…However, the success of ESWL in removing stones also depends on the specific location of the stone. 22 However, it is important to note that multiple sessions of ESWL may be required for successful removal. 23 In such cases where multiple sessions are necessary, other auxiliary approaches such as stenting may be beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…However, the success of ESWL in removing stones also depends on the specific location of the stone. 22 However, it is important to note that multiple sessions of ESWL may be required for successful removal. 23 In such cases where multiple sessions are necessary, other auxiliary approaches such as stenting may be beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies in the published literature have reported the rate of stone clearance as high as 70-100% for density <500 HU, which decreases to 66-93% for 500-1000 HU and further decreases to 33-51% for >1000 HU. 13,14,22,23 In this study we also analyzed the sub-group of patients with a stone density of 500-750 HU and 751-1000 HU which showed a success rate of 88.5% (23/26) and 41.7% (20/48) respectively. The difference in stone clearance was significant (X2 value =14.1, p=0.0008) in a present study showing a stone clearance decreasing from 100% for <500 HU to 88.5% for >500-750 HU, and further decreased to 41.7% for >751 HU for the renal and upper ureteric stones.…”
Section: Discussionmentioning
confidence: 99%